Comparison of different dwell point policies for SP-AS/RS - Vasili, Mohammad Reza; Homayouni, S. Mahdi; Tang, Sai Hong; Ismail, Napsiah (Federation of Engineering Institutions of Islamic Countries, 2006)
Stacker cranes used by the conventional AS/RS are not adequate for handling heavy loads such as sea container cargo. However, for such applications, to handle extra heavy loads (such as loads above 20 tons) at high speed, a split-platform AS/RS or SP-AS/RS for short is proposed by researchers. In the case of travel time of split platform AS/RS, it can be found that only one perfect travel time model on the previous researches was published, which was under stay dwell point policy. But it is not logical to select this travel time model as the base, without any analysis of other travel time models (under different dwell point policies). In this paper the authors develop two perfect travel time models under return to middle point and return to start point, dwell point policies. Models are validated by computer simulations and the results of different models are compared.The results show that stay dwell point policy outperforms other dwell point policies.